2018
DOI: 10.3892/etm.2018.6634
|View full text |Cite
|
Sign up to set email alerts
|

Naringin promotes cellular chemokine synthesis and potentiates mesenchymal stromal cell migration via the Ras signaling pathway

Abstract: Directional migration of mesenchymal stem cells (MSCs) is known to serve roles in bone fracture healing. Naringin is a traditional medicine used in China to treat bone injury and has been confirmed to act as a chemoattractant to MSCs. In the present study, the secretion of chemokines and stimulation of relevant signaling pathways by naringin were detected to determine the molecular mechanism of naringin-induced MSC migration. In these experiments, Quantibody® arrays were used to detect chemokines secreted by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…28 Lin et al demonstrated that the Ras family was remarkably activated by naringin. 29 Furthermore, the ERK 1/2 pathway can regulate osteogenic differentiation through microRNA. 30 Meanwhile, GelMA hydrogels and collagen have also been demonstrated to regulate the osteogenic differentiation of MSCs via ERK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…28 Lin et al demonstrated that the Ras family was remarkably activated by naringin. 29 Furthermore, the ERK 1/2 pathway can regulate osteogenic differentiation through microRNA. 30 Meanwhile, GelMA hydrogels and collagen have also been demonstrated to regulate the osteogenic differentiation of MSCs via ERK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, total flavonoids of DR could promote osteogenic differentiation of rat dental pulp stem cells via the PI3K/Akt pathway [42]. Lin et al found that the effect of naringin on the healing of fracture may be related to the promotion of the synthesis and secretion of cellular chemokines (CXCL5, CXCL6) and enhancement of mesenchymal stromal cell migration through Ras signaling pathway [43]. In addition, naringin stimulates angiogenesis by regulating the VEGF/VEGFR-2 signaling pathway in rats, thereby promoting fracture healing [38].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, researchers have been focused on improving the condition for MSC recruitment by using biological agents. Clinical-standard platelet products loaded membranes [7] and naringin [8] successfully support MSC colony formation and promote MSC migration in vitro.…”
Section: Introductionmentioning
confidence: 94%